1997
DOI: 10.1590/s0100-879x1997000100018
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex and chemoreflex dysfunction in streptozotocin-diabetic rats

Abstract: Several investigators have demonstrated that streptozotocin (STZ) diabetes induces changes in the autonomic control of the cardiovascular system. Changes in cardiovascular function may be related to peripheral neuropathy. The aim of the present study was to analyze changes in heart rate (HR) and arterial pressure (AP) as well as baroreflex and chemoreflex sensitivity in STZ-induced diabetic male Wistar rats (STZ, 50 mg/kg, iv, 15 days). Intra-arterial blood pressure signals were obtained for control and diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
59
0
15

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 15 publications
11
59
0
15
Order By: Relevance
“…Interestingly, the increase of ΔHR/ΔMABP, an indicator of BRS, was greater in DM rats compared with Ctr rats in response to PE and SNP injections. This result is not consistent with those of some DM models, which may be largely attributed to the different time course of development for diabetes (ie, 12, 24, and 48 weeks): metabolic disorders caused by a hyperglycemic state or insulinopenia may be related to time-dependent changes in parasympathetic and sympathetic control [25,26] and different osmotic diuresis after the DM model was established [27,28] . In addition, discrepancies in species, experimental design and diabetic inducer may also affect the results to some extent [29,30] .…”
Section: Discussionmentioning
confidence: 60%
“…Interestingly, the increase of ΔHR/ΔMABP, an indicator of BRS, was greater in DM rats compared with Ctr rats in response to PE and SNP injections. This result is not consistent with those of some DM models, which may be largely attributed to the different time course of development for diabetes (ie, 12, 24, and 48 weeks): metabolic disorders caused by a hyperglycemic state or insulinopenia may be related to time-dependent changes in parasympathetic and sympathetic control [25,26] and different osmotic diuresis after the DM model was established [27,28] . In addition, discrepancies in species, experimental design and diabetic inducer may also affect the results to some extent [29,30] .…”
Section: Discussionmentioning
confidence: 60%
“…The bradycardic response to methacholine injection was similar in control and diabetic rats 5 days after STZ administration (14). However, in 15-day STZ-treated rats this response was higher than in normal rats (10), suggesting that the early impairment in vagal tonus may be leading to an adaptive change in muscarinic receptors. Kuntscherova and Vlk (19) found decreased acetylcholine concentrations in isolated auricles of diabetic rats and Tomlinson et al (11) observed functional defects in cardiac cholinergic nerves in diabetic rats with vagal dysfunction.…”
Section: Autonomic Control Of Heart Rate In Experimental Diabetesmentioning
confidence: 86%
“…Hence, the disorders in autonomic efferent and afferent neuronal systems could have important consequences for the control of cardiovascular function. Several studies using experimental models have been conducted to investigate the mechanisms of reflex dysfunction of diabetes (10,(14)(15)(16)33,34).…”
Section: Baroreflex Control In Experimental Diabetesmentioning
confidence: 99%
See 2 more Smart Citations